An Analysis of the Influence of Culture on Need Hierarchies in Three Baltic Countries - Mockaitis, Audra I.; Šalčiuvienė, Laura (Ekonomika, 2003)
This paper presents the results of a two-part study, which identifies Lithuanian cultural dimensions, through extension of Hofstede’s (1980) study to this country, and uses these dimensions to predict motivational need hierarchies in three countries - Lithuania, Estonia and Poland. It is argued that national cultural values largely determine human needs (motivation theory is not universal), and that needs may be predicted by analyzing the relative positions of countries on the cultural dimensions and the interaction of different dimensions. It is also stressed that the relationship between culture and organizational attitudes may only be wholly revealed by applying a truly cross-cultural methodology. The paper begins with an overview of some of the earlier comparative studies on motivation needs and goals. Maslow has argued that his theory is applicable across all cultures, an argument which has been challenged by several researchers since the 1960s. Although these studies all revealed cross-national differences in human needs and goals, which the authors attributed to national cultural differences, in none of the studies was there sufficient evidence to support these claims. The theoretical and hypothetical relationship between culture and motivation is discussed next, by examining Hofstede’s cultural dimensions framework and the influence of these dimensions on different aspects of motivation. It is argued that only in highly individualist societies, displaying a low uncertainty avoidance, will the hierarchy of human needs resemble that of Maslow. The results of an earlier study, identifying the relative position on Lithuanian cultural dimensions, and comparing these to Polish and Estonian scores, is briefly presented. This study forms the basis from which the relative country positions on motivation factors are hypothesized and tested. According to this study, Lithuania scores relatively high on masculinity, has a medium high uncertainty avoidance, medium high individualism and medium low power distance position. Poland and Estonia score equally high on individualism, Lithuania and Estonia are similar in position on power distance and uncertainty avoidance, while Poland scores high on both of these dimensions. And while Estonia scores very low on masculinity, Lithuanian and Polish positions on this dimension are both similarly high. The results of the second study, identifying the importance placed on various needs by Lithuanian, Estonian and Polish respondents, are presented in the final parts of the paper. The study used a carefully chosen methodology, employing a matched samples strategy, ensuring, through the application of various statistical techniques as well, that any differences in country mean scores are attributed to national cultural differences. The methodology is described in a separate section in detail. Factor analysis of questionnaire items was conducted, and etic dimensions were obtained, which were shown to be reliable in each country, while the factor solution was found to closely resemble Maslow’s categories of human needs, adding validity to his theoretical categories. However, it was seen that in none of the countries does the hierarchy of human needs resemble Maslow’s, thus refuting his assertion that higher and lowerorder needs are in fact universal. In Poland, for example, the self-realization factor ranked last in importance, while in Estonia, the social needs factor ranked first It is shown that human needs in each country are predictable, by applying Hofstede’, framework, and that the main determinant of human needs is culture, the effects of which were revealed to be strong on all of the obtained motivation factors. The main goals and results of the paper may be summarized as follows. The paper was based on the assumption that motivation is largely influenced by national culture. Although many earlier studies merely attributed any obtained attitudinal differences in mean scores to national or cultural differences without proving that this is so, this study went a step further, proving that national cultural values do in fact have a significant influence on the motivational attitudes of organizational members. A strong effect of culture was found on four of five of the dependent variables: self-actualization, esteem, social and security needs. How culture influences attitudes was also analysed, by relating obtained country mean positions to cultural dimensions. It was shown that individualism, masculinity and uncertainty avoidance influence the self-actualization factor, the interaction between power distance and masculinity affects esteem needs, individualism and masculinity influence social needs and uncertainty avoidance is strongly related with the importance places on security needs. All of the hypotheses presented were confirmed, as the predicted country positions on the dependent variables were similar to country positions on cultural variables. However, this was not yet considered to be sufficient evidence of the effect of culture on the dependent variables. This was further proven by directly relating culture to the dependent variables, by measuring the extent of culture’s influence on the results before and after the introduction of covariates in the ANOVA. It was found that culture’s influence on all factors was significant, while demographic variables partially explained mean differences on a few variables. Thus, the main hypothesis of the paper, that is, that needs are determined by culture, is confirmed. The second goal of the paper was to test the application of west em management theories (e. g. Maslow’s need hierarchy) in the post-soviet context The results confirmed that need categories as such do exist in these countries, as has been shown in previous studies as well, however, the ranking of need importance differs in each of the countries. It is concluded that Maslow’s theory is not in fact universal, and it is recommended that academics and practitioners consider context and the relationship between culture and management attitudes when applying such theories in practice. It is hoped that this study will contribute to a fuller understanding of the methodological requirements of cross-cultural research. It is recommended that in conducting such studies in the future. researchers analyze not only country differences on the object of study but also begin more and more to isolate and directly measure the causes of such differences.